1998
DOI: 10.1007/s007010050236
|View full text |Cite
|
Sign up to set email alerts
|

Primary Meningeal Malignant Fibrous Histiocytoma with Cerebrospinal Dissemination and Pulmonary Metastasis

Abstract: Primary intracranial malignant fibrous histiocytoma (MFH) is very rare, and not much is known about its clinical features. The authors report a case of left temporal leptomeningeal MFH, with consequent cerebrospinal fluid (CSF) dissemination and pulmonary metastasis. The clinical features of this case and the therapeutic prognosis of 17 cases reported previously in the literature were reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A few of the published reports of primary intracranial MFH have included MRI findings in their description of the tumor; however, the MRI findings were limited to conventional magnetic resonance (MR) sequences, such as T1‐ and T2WI and contrast‐enhanced T1WIs 1–3,8,9 . Central necrosis and surrounding edema, as observed on T2WIs, revealed markedly high and intermediately high signal intensity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A few of the published reports of primary intracranial MFH have included MRI findings in their description of the tumor; however, the MRI findings were limited to conventional magnetic resonance (MR) sequences, such as T1‐ and T2WI and contrast‐enhanced T1WIs 1–3,8,9 . Central necrosis and surrounding edema, as observed on T2WIs, revealed markedly high and intermediately high signal intensity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Even with aggressive chemotherapy and radiation, median survival was only 27 months due to local progression with occasional metastasis and cerebrospinal fluid dissemination according to Hamlat et al’s series [8]. Doxorubicin and ifosfamide have been used in the treatment of intracranial UPS due to their activity against soft tissue sarcomas as reported by Akimoto et al [9]. Ham et al, reviewed the use of a high-dose methotrexate-based regimen in 17 cases of bone UPS, and they found that it dropped the recurrence/metastasis rate from occurring at an average of 17 months to no recurrence during an average follow-up period of 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial MFH does not have specific radiological features on MRI and CT images due to its variable degrees of histological differentiation [15] . Arteriography of the tumor can be vascular or avascular [34,35] . Tumors appear hypermetabolic on PET-CT scan, just like other malignant tumors [15] .…”
Section: Discussionmentioning
confidence: 99%